2020
DOI: 10.1088/1361-6595/ab681b
|View full text |Cite
|
Sign up to set email alerts
|

Electron number density measurements in nanosecond repetitively pulsed discharges in water vapor at atmospheric pressure

Abstract: This article reports on experiments in a nonequilibrium plasma produced by nanosecond repetitively pulsed (NRP) spark discharges in water vapor at 450 K and atmospheric pressure. The objective is to determine the electron number density in the post-discharge, with spatial and temporal resolution, to gain a better understanding of the discharge development and chemical kinetics. Electron number densities were measured in water vapor from the broadenings and shifts of the H α … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 36 publications
5
17
0
Order By: Relevance
“…The measurements clearly show that the main broadening effect is due to the Stark effect. This approach was already used by Sainct et al [11] to confirm that, in their work, the measured H broadening widths were due to the Stark effect. Based on our measurements, we find that the lines at 519 nm are well fitted using Eq.…”
Section: Discussionsupporting
confidence: 58%
“…The measurements clearly show that the main broadening effect is due to the Stark effect. This approach was already used by Sainct et al [11] to confirm that, in their work, the measured H broadening widths were due to the Stark effect. Based on our measurements, we find that the lines at 519 nm are well fitted using Eq.…”
Section: Discussionsupporting
confidence: 58%
“…The different states of non-equilibrium NRP plasmas (corona, glow, and spark) have been described by Pai et al [2]. However, other works [7][8][9][10][11][12][13][14] have shown that nanosecond discharges can also produce fully ionized thermal plasmas. This type of nanosecond discharge, called the thermal spark, is in thermal equilibrium [7] and differs from the NRP spark described by Pai et al [2].…”
Section: Introductionmentioning
confidence: 95%
“…The error bars indicate estimated uncertainties of our calculations. The results presented above are based on the assumption of a stationary diagonal density matrix, see Equation (6). This is, however, not necessarily the case with nearly resonant laser pumping of sufficient magnitude.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, in that study a plasma filament was formed by a femtosecond Ti:sapphire (λ = 805 nm) laser pulse in air. On the other hand, a very recent experimental study of Sainct et al [6] found a fair agreement in the density determined from the Stark broadening of the O I 777-nm line and that of hydrogen Balmer-α and -β in pulsed discharges at atmospheric pressure. The typical electron density in this case was 1-2 orders of magnitude higher than in [4,5], though.…”
Section: Introductionmentioning
confidence: 85%